PENGARUH MEMBACA AL-QURAN TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI UPT PELAYANAN SOSIAL LANJUT USIA KISARAN - RANTAU PRAPAT TAHUN 2017 - Alamsyah Lukito (Universitas Muhammadiyah Sumatera Utara, 2018)
Management for hypertensive patients can be given pharmacologically and nonpharmacologically For non-pharmacological therapy, usually patients with hypertension is recommended for healthy lifestyle and reduce stress with relaxation. Reading Al-Quran is a religious relaxation that is beneficial to health. This study aims to determine the effect of reading Al-Quran on blood pressure in the elderly with hypertension performed in UPT Senior Age Social Service. The method used is quasi experiment with control group pretest-posttest design, sample taken using purposive sampling technique.Respondents of this study add up to 34 people with an age range of 50-86 years. 47.05% male and 52.94% female. The results of this study reported a decrease in systolic and diastolic blood pressure of the intervention group (p <0.05) and reported significant differences in blood pressure values between intervention group and control group (p <0.05). The conclusion is there is the influence of reading the Quran with the decrease in blood pressure in the elderly with hypertension. Keywords : reading Al-Quran, Al-Quran, elderly, blood pressure, hypertension.